Pelatihan Pembuatan Sabun Cuci Piring dan Pakaian Berbahan Eco-Enzyme sebagai Upaya Pemberdayaan Masyarakat - Paujiah, Epa; Hartati, Sri (GEN ID, 2025)
This training aims to enhance community knowledge and skills in starting a business through interactive and practical education. The methods used include counseling, hands-on practice, and discussion sessions to ensure participants' understanding of the provided materials. Evaluation results indicate that the training had a positive impact on participants. 94% of participants reported gaining new knowledge, while 92% felt more confident in starting a business. Additionally, 88% stated that the materials were easy to understand, and 96% found the training beneficial for their daily lives. In terms of facilities, 94% considered the provided resources adequate to support the training. Furthermore, 87% believed the training could improve their family's well-being, and 91% felt that its benefits could extend to the surrounding community. The training outcomes are expected to make a meaningful contribution to enhancing skills and economic well-being within the community.